Perbandingan Hukum Pidana Perzinaan di Malaysia dan Brunei Darussalam - Sudarti Sudarti (El-Mashlahah, 2021)
Malaysia and Brunei Darussalam are country which is being in  Southeast Asia Area, the majority is population of religion islam. Both of them have equality and difference in applying islamic law about criminal sanction in adultery such as contained in Enakmen Jenayah Syariáh Selangor Number 9 in 1995 and Kanun Jenayah Syariáh Brunei Darussalam.  The research is aim to analysis the problem of criminal sanction in adultery Enakmen Syariáh Selangor Number 9 in 1995 and Kanun Jenayah Syariah Brunei Darussalam that used maqasid syariah such as methodology. Type of research will  be used library research by  analytical descriptive method. The results show the aspect of daruriyyah, who applied by punishment for the adultere are the aspect of keeping offspring  (hifdz al-asl). The aspect is related to children’s rights and  the civil relationship between a child with their biological parents.